FRI0361 The Extension of Inflammatory Infiltrates or Intimal Hyperplasia in Temporal Arteries Do Not Significantly Predict CTA-Detection of Aortic Thickening in Newly-Diagnosed Patients with biopsy-proven Giant-Cell Arteritis. (15th July 2016) - Murgia, G.; Hernández-Rodríguez, J.; Prieto-González, S.; García-Martínez, A.; Espigol-Frigole, G.; Alba, M.A.; Villar, I.; Campo, E.; Arguis, P.; Gilabert, R.; Grau, J.M.; Cid, M.C.
Abstract : Background: Giant cell arteritis (GCA) is a granulomatous vasculitis preferentially targeting the carotid and vertebral artery branches. Aortic involvement is common and may lead to severe complications such as aortic dilatation/aneurysm or dissection 1 . While small necropsy studies detected histopathologically-proven aortic inflammation in more than 90% of patients, aortic wall thickening suggesting aortitis is detected in 65% of patients using CTA at diagnosis 2 . We hypothesized that histological features underlying arterial wall thickening (transmural inflammatory infiltrate or intimal hyperplasia) observed in temporal artery biopsies might predict CTA-detection of aortic wall involvement. Objectives: To assess whether the extension of inflammatory infiltrates and/or the degree of intimal hyperplasia in temporal artery biopsies (TAB) from GCA patients correlate with CTA detection of aortitis at the time of diagnosis. Methods: TABs from biopsy-proven GCA included in an ongoing prospective study for detection of large vessel vasculitis (LVV) at diagnosis 1 were scored for the extent of inflammatory infiltrates or intimal hyperplasia as described 3 . Aortitis was defined by CTA as concentric thickening of the aortic wall ≥2mm. TABs were categorized according to the extent of inflammatory infiltrates (inflammation limited to adventitia vs transmural inflammation) and the degree of intimal hyperplasia. The latter was considered mild/moderate or severe depending on the ratio between the maximal thickness of the intima layer and the distance between the center of the lumen and the internal elastic lamina (<75%vs>75%). Fisher exact test was used for statistical analysis. Results: Between November 2006 and June 2013, 51 patients diagnosed with biopsy-proven GCA were included in a CTA-based screening protocol for LVV. Overall, aortitis was detected by CTA in 34 (66.7%) of cases. Inflammation limited to the adventitia was observed in 10 (19.6%) of cases and transmural inflammation in 41 (80.4%). Mild/moderate intimal hyperplasia was observed in 17 (33.3%) biopsies and severe intimal hyperplasia in 34 (66.7%). CTA-detected aortitis was observed in 27 (79.4%) of patients with transmural inflammation compared with 7 (70%) of patients with inflammation limited to the adventitia (p=1.00). Aortitis was seen in 23 (67.6%) of patients with severe intimal hyperplasia compared to 11 (64.7%)of patients with mild/moderate neointima formation (p=1.00). Conclusions: Although the limited size of this cohort prevents definitive conclusions, the extension of inflammatory infiltrates or intimal hyperplasia in temporal arteries do not significantly predict CTA-detection of aortic thickening in GCA. Variability in the distribution of lesions along the vascular tree may account for these findings. Supported by Marato TV3 2014/201507. References: García-Martínez A et al Ann Rheum Dis 2014 Prieto-González S et al Ann Rheum Dis 2012 Hernández-Rodríguez J et al Medicine 2016 Disclosure of Interest: None declared